Development of pre-service mathematics teachers’ professional knowledge and identity in working with information and communication technology - Ponte, João Pedro da (2011)
This paper describes the work undertaken in a course in communication and information technology in a pre-service program for secondary school mathematics teachers. This course aimed to help pre-service teachers develop a positive attitude regarding ICT and use it confidently. It focused on the exploration of educational software and of the Internet’s potential as a means of research and production of web sites. We discuss how the pre-service mathematics teachers evaluate their work concerning their commitment, difficulties they found, learning they identified, and personal relationship. We also analyse the effects of the course on the development of their professional knowledge and identity.